Brain Abscess Mimicking Intracranial Extension Of Nasopharyngeal Carcinoma - Idris, R; Mohamad, I (Bangladesh Journal of Medical Science, 2012)
With the advent of more effective but aggressive cancer treatment regimens, survival in many types of cancer has improved including nasopharyngeal carcinoma (NPC). Radiotherapy (RT) is still the mainstay of treatment for patients with NPC. Unfortunately, it has led to several new complications of cancer and its therapy. One of the most important complications is central nervous system (CNS) infections. We report a case of NPC presented with signs of increased intracranial pressure making the diagnosis of intracranial extension of NPC. Imaging studies later on proved that it was an abscess which responded well with conservative medical treatment. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11741 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12